Big trouble in little Greektown - Collins, Kate, 1951- (Collins, Kate, 1951- Goddess of Greene St. mysteries., 2021)
When she attends a fundraiser and art festival with her date, Case Donnelly, who is awaiting his PI license, Athena Spencer puts him to good use when the body of a disgraced photographer turns up during a nature walk.